Pengawasan Instruksi Bupati Banyuasin Nomor 1564 Mengenai PPKM Pada Level Desa di Desa Saleh Mukti Kecamatan Air Salek Kabupaten Banyuasin - Dian Cahyaningtyas; Amaliatulwalidain Amaliatulwalidain; M. Qur’anul Kariem (Pencerah, 2022)
The purpose of this study was to determine the supervision of the instruction of the Banyuasin Regent Number 1564 regarding PPKM at the Saleh Mukti Village Level, Air Salek District, Banyuasin Regency. Data collection techniques were obtained directly from research informants, in the form of interview results. The results of the research indicator set school standards for carrying out the regent's instructions, namely teachers and students are required to carry out the obligation to use 3M, namely washing hands, maintaining distance, and wearing masks. In addition, the restrictions on face-to-face learning hours are also reduced shorter than in normal conditions. Supervision is carried out at places of worship, where worshippers must discipline themselves in carrying out worship such as wearing masks, maintaining distance, and washing hands. By regent's regulation number 1564 of 2021, the village of Saleh Mukti out of 16 regent rules has optimized but only 8 standards have been achieved. The instructions of the regent of the pious village community felt confused about what to do, it seemed that the community followed the rules seen from television, and information through social media, and at the previous time the regent's instructions still looked unremarkable. After the instructions were imposed, residents obeyed the instructions of the Banyuasin Regent Number 1564 of 2021. Enforcement for people who do not comply with the regulations is carried out by reprimanding, and socialization is carried out to the community to always comply with existing regulations. If there is a situation that causes crowds, the village government, police officers, and the Covid-19 task force will disperse the existing crowds. This is a deterrent effect for people who do not comply with the rules that have been put in place.